A continent for peace and science: Antarctic science and international politics from the 6th International Geographical Congress to the Antarctic Treaty (1895-1959) - Cardone, Ignacio Javier (2019)
In order to understand how and why the white continent ended up being reserved for peaceful use, scientific investigation and international cooperation, this thesis analyses the history of Antarctic international relations between the 6th International Geographical Congress and the signature of the Antarctic Treaty. Following Giddens\' Theory of Structuration, Adler & Pouliot´s communities of practice perspective and Haas and Adler´s epistemic community concept, the following research proposes a multi-level and multi-dimensional framework aimed to overcome the limitations of the usual interpretations of the origins of the Antarctic regime. Making use of archival material from Argentina, Australia, Chile, the United Kingdom and the United States of America, this research emphasizes the role that science played in the international relations related to Antarctica along with political, economic and ideational aspects. Through the following pages I show how the initial impetus for Antarctic exploration originated rather in a sincere scientific desire, than in any geopolitical interest in the Southern regions. The latter would only develop once the economic interest was fostered by the emergence of Antarctic whaling, which would install a logic of territorial competition. Eventually, the instrumentalisation of science by the political interest would both limit the freedom of manoeuvre of scientists and scientific institutions but also allowed them to develop a more intensive Antarctic programme and influence the political decision-making process. It would be eventually the scientific community, through the promotion of international cooperation during the International Geophysical Year, who would enable to search a viable political formula to settle the Antarctic question. However, only when favourable circumstances were combined with the presence of a constituted international epistemic Antarctic community, the structured values attached to the Antarctic activity could be crystallized in principles incorporated in an international agreement for Antarctica. At last, the role of science and the values attached to its practice were recognized in the Antarctic Treaty, while at the same time the exclusivity of the political sphere on Antarctic questions was demanded by the nation-state governments, relegating scientists and scientific institutions to their fields of expertise and guaranteeing the conditions through which their practice could be satisfied. Considering that, the Antarctic regime appears as a crystallization of a complex and extensive sociological process in which science played a key role and, the same time, acknowledged the position of the state as the prominent political actor in Antarctica.